Displacement, Velocity and Distance Travelled by Natural Logarithmic Equations

A particle is moving in a straight line, starting from the origin. At time \( t \) seconds the particle has a displacement of \( x \) metres from the origin and a velocity \( v \ \text{m s}^{-1} \).
The displacement is given by \( x = 3t – 6 \log_e (t+1) \).

Part 1

Find the expression for the velocity, \( v \).

\( \begin{align} \displaystyle v &= \frac{dx}{dt} \\ &= \frac{d}{dx} 3t – 6 \frac{d}{dx} \log_e (t+1) \\ &= 3 – 6 \times \frac{1}{t+1} \\ &= 3 – \frac{6}{t+1} \end{align} \)

Part 2

Find the initial velocity.

\( \begin{align} \displaystyle v (t=0) &= 3 – \frac{6}{0+1} \\ &= -3 \end{align} \)

Part 3

Determine the initial direction of the particle.

Moving backward as \( v = -3 \lt 0 \)

Part 4

Find when the particle comes to rest.

Particle comes to rest when \( v=0 \)
\( \displaystyle \begin{align} 3 – \frac{6}{t+1} &= 0 \\ -\frac{6}{t+1} &= -3 \\ \frac{6}{t+1} &= 3 \\ t+1 &= 2 \\ t &= 1 \end{align} \)

Part 5

Find the distance travelled for the first second.

\( \displaystyle \begin{align} x(t=0) &= 0 \\ x(t=1) &= 3 \times 1 – 6 \log_e (1+1) \\ & = 3 – 6 \log_e 2 \lt 0 \\ \text{distance travelled} &= 6 \log_e 2 -3 &\color{green}{\cdots \text{moving backward} } \end{align} \)

Part 6

Find the distance travelled that the particle comes back to the origin.

\( 2 \times (6 \log_e 2 – 3) = 12 \log_e 2 – 6 \)

Part 7

Find the displacement at \( t = 4 \).

\( \begin{align} \displaystyle x(t=4) &= 3 \times 4 – 6 \log_e (4+1) \\ &= 12 – 6 \log_e 5 \end{align} \)

Part 8

Find the distance travelled by the particle in the first four seconds.

\( \begin{align} (12 \log_e 2 – 6) + (12 – 6 \log_e 5) &= 6 + 12 \log_e 2 + 6 \log_e 5 \\ &= 23.974 \cdots \text{metres} \end{align} \)

Absolute Value Algebra Arithmetic Mean Arithmetic Sequence Binomial Expansion Binomial Theorem Chain Rule Circle Geometry Combinations Common Difference Common Ratio Compound Angle Formula Compound Interest Cyclic Quadrilateral Differentiation Discriminant Double-Angle Formula Equation Exponent Exponential Function Factorials Functions Geometric Mean Geometric Sequence Geometric Series Inequality Integration Kinematics Logarithm Logarithmic Functions Mathematical Induction Probability Product Rule Proof Quadratic Quotient Rule Rational Functions Sequence Sketching Graphs Surds Transformation Trigonometric Functions Trigonometric Properties VCE Mathematics Volume

 



Your email address will not be published. Required fields are marked *